2023
DOI: 10.3390/pr11010244
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Fire Prevention Technologies by Cause of Fire: Selection of Causes Based on Fire Statistics in the Republic of Korea

Abstract: Every year, diverse types of safety accidents cause major damage to human life and property. In particular, failure to suppress safety accidents caused by fires during the early stages can lead to large-scale accidents, which in turn can cause more serious damage than other types of accident. Therefore, this paper presents an analysis of the prevailing research trends and future directions for research on preventing safety accidents due to fire. Since fire outbreaks can occur in many types of places, the study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
0
2
0
Order By: Relevance
“…Wet chemical extinguishers, designed for class K fires, often use a potassium-based solution with a low environmental impact. 3,4 Halon fire extinguishers were historically employed for class B fires, renowned for their efficacy in quelling fires involving flammable liquids and gases, rendering them suitable for class B fire hazards. Halon, functioning as a clean agent, disrupts the chemical reaction of the fire without leaving residue, proving particularly advantageous in environments housing sensitive equipment or materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wet chemical extinguishers, designed for class K fires, often use a potassium-based solution with a low environmental impact. 3,4 Halon fire extinguishers were historically employed for class B fires, renowned for their efficacy in quelling fires involving flammable liquids and gases, rendering them suitable for class B fire hazards. Halon, functioning as a clean agent, disrupts the chemical reaction of the fire without leaving residue, proving particularly advantageous in environments housing sensitive equipment or materials.…”
Section: Introductionmentioning
confidence: 99%
“…Dry powder extinguishers, versatile for class A, B, C, and D fires, may have varying environmental impacts based on their formulation. Wet chemical extinguishers, designed for class K fires, often use a potassium-based solution with a low environmental impact. , …”
Section: Introductionmentioning
confidence: 99%
“…For this reason, it has made it compulsory to organize large‐scale training in all institutions (Xiong et al, 2023). Training has been shown as one of the four basic strategies of fire safety with a similar policy as of 2023 in Korea (Lee et al, 2023). However, when the literature is examined in detail, although it is mentioned that trainings are important, it is seen that the construction and design risks of the places with fire risk come to the fore and the evaluations about the trainings are neglected.…”
Section: Introductionmentioning
confidence: 99%
“…The most important cause of fires, which cause many loss of life and property every year, is faulty human behaviour. In Korea, it has been reported that half of the country's fire statistics are due to negligence (Lee et al, 2023).…”
Section: Introductionmentioning
confidence: 99%